Exercise and Asthma - Côté, Andréanne; Turmel, Julie; Boulet, Louis-Philippe (Seminars in Respiratory and Critical Care Medicine, 2018)
Transient airway narrowing can occur during or following exercise, a phenomenon called exercise-induced bronchoconstriction (EIB). The main mechanism of EIB is considered to be airway dehydration, resulting from increased ventilation during exercise. In asthma, such water loss causes an increase in airway fluid osmolarity, inducing airway smooth muscle contraction following the release of mediators from airway inflammatory cells. Asthmatics frequently experience EIB, but it may also be observed in others not reporting asthma symptoms, particularly elite endurance athletes. Individuals with asthma often refrain from performing physical exercise because they fear troublesome respiratory symptoms. However, in addition to its well-known cardiovascular and metabolic benefits, physical training has been shown to be beneficial for asthmatic adults and children in improving asthma control and asthma-related quality of life. Exercise training also reduces the risk of asthma exacerbations, improves exercise capacity, and decreases frequency and severity of EIB. To minimize the risk of EIB, asthma must be well controlled, and specific pharmacological and nonpharmacological preventative measures can be taken. Counterintuitively, in high-level athletes, the development of asthma, airway hyperresponsiveness, and EIB can be promoted by intense training over many years following exposure to environmental conditions, such as cold air, pollutants, and allergens. As for nonathletes, athletes must have optimal asthma control and apply preventative measures against EIB, taking into account antidoping regulations for asthma medications. A better understanding of the impact of exercise on asthma should improve the overall care of asthmatic patients.
Keywords: asthma; exercise; exercise-induced bronchoconstriction; physical training; athletes